Media industry studies - Herbert, Daniel 1974-; Lotz, Amanda D. 1974-; Punathambekar, Aswin (Short introductions, 2020)
The origins of media industry studies -- Individuals and roles -- "Production" cultures -- Organizations -- Industries and practices -- The macro view -- Conclusion : future directions for media industry studies